2006
DOI: 10.1021/jm0510934
|View full text |Cite
|
Sign up to set email alerts
|

2,4-Diaminopyrimidine Derivatives as Potent Growth Hormone Secretagogue Receptor Antagonists

Abstract: Ghrelin, a gut-derived orexigenic hormone, is an endogenous ligand of the growth hormone secretagogue receptor (GHS-R). Centrally administered ghrelin has been shown to cause hunger and increase food intake in rodents. Inhibition of ghrelin actions with ghrelin antibody, peptidyl GHS-R antagonists, and antisense oligonucleosides resulted in weight loss and food intake decrease in rodents. Here we report the effects of GHS-R antagonists, some of which were potent, selective, and orally bioavailable. A structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 34 publications
4
45
0
Order By: Relevance
“…If the increase in seizure threshold is due to the loss of constitutively active GHSR receptors, rather than a developmental consequence of the absence of the receptor throughout the life of the GHSR -/-mice, then it may be possible to mimic the effects by inactivating the GHSR. We started investigating the pharmacological properties of the presumed GHSR antagonist A778193, which has a nanomolar affinity for the GHSR [35]. Using HEK293 cells expressing the cloned hGHSR, we found that A778193 in fact acts as a potent inverse agonist with a pIC 50 of 6.13±0.22 (n03) (Fig.…”
Section: Ghsr -/-Mice Are Less Susceptible To Limbic Seizures With Sementioning
confidence: 99%
“…If the increase in seizure threshold is due to the loss of constitutively active GHSR receptors, rather than a developmental consequence of the absence of the receptor throughout the life of the GHSR -/-mice, then it may be possible to mimic the effects by inactivating the GHSR. We started investigating the pharmacological properties of the presumed GHSR antagonist A778193, which has a nanomolar affinity for the GHSR [35]. Using HEK293 cells expressing the cloned hGHSR, we found that A778193 in fact acts as a potent inverse agonist with a pIC 50 of 6.13±0.22 (n03) (Fig.…”
Section: Ghsr -/-Mice Are Less Susceptible To Limbic Seizures With Sementioning
confidence: 99%
“…In present study 2, 4-diaminopyrimidine derivatives (Table I) have been taken from the literature report [16] along with their antagonistic activity. The activity was expressed as the logarithm of the inverse of inhibitory concentration, pIC 50 , where IC 50 represents the molar concentration, required to bring out 50% inhibition of GHS-R. Two different approaches, namely the non-parametric and the parametric, have been used to develop the important QSARs of titled compounds.…”
Section: Data Setmentioning
confidence: 99%
“…However, these compounds did not exhibit an effect when tested in in vivo animal models. More recently, a synthetic study was performed [16] on the derivatives of 2,4-diaminopyrimidine and to identify them as effective GHS-R antagonists. These compounds were first run in the GHS-R binding assays and were further investigated in an intracellular Ca +2 flux activity assay.…”
Section: Introductionmentioning
confidence: 99%
“…Through its action on growth hormone secretagogue receptor type 1a, ghrelin exerts a variety of metabolic functions including stimulation of growth hormone release, stimulation of appetite and weight gain, and suppression of insulin secretion in rodents and humans (Nakazato et al, 2001;Wren et al, 2001;Dezaki et al, 2008;Cardona Cano et al, 2012;Heppner et al, 2012). Thus, antagonizing growth hormone secretagogue receptor (GHSR)-1a with small molecule antagonists or inverse agonists is anticipated to improve glucose homeostasis and insulin sensitivity, while eliciting beneficial effects on body weight (Serby et al, 2006;Esler et al, 2007;Rudolph et al, 2007;Soares et al, 2008;Costantino and Barlocco, 2009).…”
Section: Introductionmentioning
confidence: 99%